2019
DOI: 10.1093/ofid/ofz321
|View full text |Cite
|
Sign up to set email alerts
|

Centralized Communication of Blood Culture Results Leveraging Antimicrobial Stewardship and Rapid Diagnostics

Abstract: Objective This study aimed to determine if integrating antimicrobial stewardship program (ASP) personnel with rapid diagnostic testing resulted in improved outcomes for patients with positive blood cultures. Method Beginning in 2016, Saint Luke’s Health System (SLHS) implemented a new process where all positive blood cultures were communicated to ASP personnel or SLHS pharmacy staff. Pharmacists then became responsible for in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 17 publications
0
5
0
Order By: Relevance
“…We extracted clinical outcome data from 57 of 301 total studies ( Fig 7 ). Of three studies that reported the proportion of patients who were admitted to the intensive care unit before and after the intervention, only one reported a statistically significant change, a decrease from 44.5% to 35.5% of patients (OR: 0.7, 95% CI: 0.5–1.0) [ 46 ]. Three separate studies reported the proportion of patients who experienced an adverse event before and after the intervention, and one reported a statistically significant change, an increase from 1.1% to 10.0% (OR: 9.9, 95% CI: 8.4–11.6) [ 47 ].…”
Section: Resultsmentioning
confidence: 99%
“…We extracted clinical outcome data from 57 of 301 total studies ( Fig 7 ). Of three studies that reported the proportion of patients who were admitted to the intensive care unit before and after the intervention, only one reported a statistically significant change, a decrease from 44.5% to 35.5% of patients (OR: 0.7, 95% CI: 0.5–1.0) [ 46 ]. Three separate studies reported the proportion of patients who experienced an adverse event before and after the intervention, and one reported a statistically significant change, an increase from 1.1% to 10.0% (OR: 9.9, 95% CI: 8.4–11.6) [ 47 ].…”
Section: Resultsmentioning
confidence: 99%
“…We extracted clinical outcome data from 57 of 301 total studies (Fig 6). Of three studies that reported the proportion of patients who were admitted to the intensive care unit before and after the intervention, only one reported a statistically significant change, a decrease from 44.5% to 35.5% of patients (OR: 0.7, 95% CI: 0.5-1.0) (44). Three separate studies reported the proportion of patients who experienced an adverse event before and after the intervention, and one reported a statistically significant change, an increase from 1.1% to 10.0% (OR: 9.9, 95% CI: 8.4-11.6) (45).…”
Section: Resultsmentioning
confidence: 99%
“…13 Moreover, the result is obtained in a much shorter period of time than in culture and is not influenced by antibiotic therapy. 15 Furthermore, in contrast to the blood culture, which is a qualitative technique, molecular techniques also allow quantitative evaluation of the sample. However, the range of commercial assays for direct testing of blood samples is limited to a few PCR tests belonging to the multiplex group or broad-range assays.…”
Section: Microbiological Diagnostics Of Bsimentioning
confidence: 99%
“…For identification of the microorganisms -sequencing, mass spectrometry (PCR/ESI-MS) or melting curve analysis (real-time PCR) may be used. 13,15 Multiplex panels enable detection of 20-34 different pathogens and single resistance genes (mainly mecA), and the result may be available within one to several hours. Systems from the group of broad-range PCR have much wider possibilities of microorganism identification, even more than 700 species, and some of them enable identification of dangerous resistance genes (mecA, vanA, vanB, bla KPC ).…”
Section: Microbiological Diagnostics Of Bsimentioning
confidence: 99%
See 1 more Smart Citation